SOCIAL BURDEN OF RHEUMATOID ARTHRITIS - I. Yu. Zinchuk; V. N. Amirdzhanova (Научно-практическая ревматология, 2014)
The paper reviews data on the incidence of rheumatoid arthritis, disability, and the cost of treatment, including thera- py with biological agents.